2007
DOI: 10.1088/1464-4258/9/6/s14
|View full text |Cite
|
Sign up to set email alerts
|

Handling unfavourable polarization states in a polarization-based shearing speckle interferometer

Abstract: A polarization-based shearing speckle interferometer requires the incoming scattered light to have proper polarization characteristics: the light should be equally distributed over two orthogonal polarization states in order to obtain two interfering beams with equal intensities and the highest possible modulation. Many surfaces scatter linearly polarized light randomly, providing equal intensities for the interfering beams on average. However, when a diffusely reflecting metallic surface is illuminated by a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…However, the actual measurement is taken according to Equation (13). To correct for the phase difference, we write cos φ and sin φ as…”
Section: Correction For Phase Differences Between Stationary and Vibrmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the actual measurement is taken according to Equation (13). To correct for the phase difference, we write cos φ and sin φ as…”
Section: Correction For Phase Differences Between Stationary and Vibrmentioning
confidence: 99%
“…The object was excited by a loudspeaker on the backside, at a frequency of 147 Hz. The speckle interferometer used was a modified subsystem of an existing shearography system . The subsystem, a polarisation‐sensitive shearing interferometer in Michelson configuration, is shown in Figure .…”
Section: Linear Regression For True Bessel‐modulated Vibration Amplitmentioning
confidence: 99%
“…Phase maps obtained using this method will have reduced spatial resolution compared to temporal phase stepping since each image occupies only a fraction of the available area on the camera's sensor, although this may not be too much of a problem if a large format sensor is used. Another system that employs spatial phase shifting involves a polarization-based shearing interferometer which divides an incoming image into two and images them side-by-side on a camera with a π relative phase shift [70]. Analysis showed that maintaining sub-pixel image registration was essential to maintain accurate measurements [71].…”
Section: Spatial Phase Steppingmentioning
confidence: 99%
“…Analysis showed that maintaining sub-pixel image registration was essential to maintain accurate measurements [71]. A more recent paper [70] discusses an improvement of the system when dealing with unfavourable polarization states. …”
Section: Spatial Phase Steppingmentioning
confidence: 99%